From stethoscope to ambient intelligence: the evolution of healthcare. (11th May 2004) - Riva, Giuseppe; Gramatica, Furio
Since the development of methods of electronic communication, clinicians have been using information and communication technologies for the exchange of health-related information. However, the evolution and increased availability of new shared media, such as the internet and virtual reality, are changing the ways in which patients and clinicians relate and communicate. To date, some e-health applications have improved the quality of healthcare, and later they will lead to substantial cost savings. For instance, physicians can review radiological films and pathology slides in remote sites, or assist and perform surgery via remote robotics. However, most of these applications are used for discrete clinical activities, such as scripting, lab-testing, patient monitoring, and condition-specific diagnostics and treatment. The next challenge is their integration within a common clinical framework able to radically change our experience of healthcare. Ambient Intelligence (AmI), a new paradigm in information technology, in which people are empowered through a digital environment that is aware of their presence and context, and is sensitive, adaptive, and responsive to their needs, habits, gestures and emotions, is the next logical step of this process. In this sense, the AmI paradigm can be seen as the direct extension of today's concept of ubiquitous computing: the integration of microprocessors into everyday objects. How does the emergence of the AmI paradigm influence the future of healthcare? Using a scenario-based approach the chapter will outline the possible role of AmI in healthcare by focusing on both its technological and relational nature. In this sense, clinicians and healthcare providers that want to successfully exploit the potential of AmI need to give significant attention to technology, ergonomics, project management, human factors and organisational changes in the structure of the relevant health service.